A versatile approach to grafting biofouling resistant coatings from polymeric membrane surfaces using an adhesive macroinitiator. Issue 77 (22nd August 2015) - Ginic-Markovic, Milena; Barclay, Thomas; Constantopoulos, Kristina T.; Al-Ghamdi, Tawfiq; Blok, Andrew; Markovic, Elda; Ellis, Amanda V.
<x xml:space="preserve">Abstract</x> The use of a polydopamine-based macroinitiator provides a flexible attachment method that is virtually independent of membrane substrate. The subsequent ARGET-ATRP controllably grafts the stable biofouling resistant polyzwitterion coating.